How does ESG explain excess returns in emerging market? An Asset-Pricing Approach - Clarissa Mulialim; Muhammad Madyan (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: Previous studies found several important risk factors for the capital market in explaining stock performance. However, most studies only consider conventional investment factors without considering sustainable ones. This study examines Environmental, Social, and Governance (ESG) performance's effect as a risk factor in a multi-factor model. Design/Methods/Approach: This study employs secondary data from the company's financial reports, annual reports, and Thomson Reuters ESG score data. The sample for this study were companies listed on the LQ45 index during the 2015-2019 period, which were selected using the purposive sampling method and produced a selection of 19 non-financial companies that met the criteria. Findings: The results show that ESG negatively affects 21 out of 30 portfolios, and the four-factor ESG model is better at explaining excess returns than the three-factor Fama-French model. Originality/Value: This study provides new insights by including ESG as a risk factor in the three-factor Fama-French model in explaining stock returns. The existence of the ESG variable allows us to identify whether sustainability is an essential determinant in explaining the average portfolio return. This study adds new insights, where using sustainability reports in the form of ESG can capture cross-sectional variations in stock returns, not only on market factors, size factors, and book-to-market factors. Practical/Policy implication: Given the established evidence that ESG factors can mitigate risk, investors are encouraged to thoroughly evaluate a company's sustainability report to assess the efficacy of its ESG performance. For managers of companies, this serves as the foundation for developing strategies that will enhance the long-term profitability and sustainability of the organization.